GE_GERICHTE C/18489/2016 vom 2. Februar 2018 - GE Cour de justice (2018)
CONTRAT DE TRAVAIL ; INTERPRÉTATION(SENS GÉNÉRAL) ; SALAIRE ; COMPENSATION DE CRÉANCES | CO.18; CO.322.al1; CO.324.al1; CO.324.al2; CO.339.al1; CO.120.al1; CO.125.al2